2016
DOI: 10.1021/acs.inorgchem.6b00909
|View full text |Cite
|
Sign up to set email alerts
|

Transforming MOFs for Energy Applications Using the Guest@MOF Concept

Abstract: As the world transitions from fossil fuels to clean energy sources in the coming decades, many technological challenges will require chemists and material scientists to develop new materials for applications related to energy conversion, storage, and efficiency. Because of their unprecedented adaptability, metal-organic frameworks (MOFs) will factor strongly in this portfolio. By utilizing the broad synthetic toolkit provided by the fields of organic and inorganic chemistry, MOF pores can be customized to suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 114 publications
0
48
0
1
Order By: Relevance
“…We here like to refer to a conceptual article on guest@MOF systems, published by Allendorf and our group . Additionally, there are other illuminating articles that specifically address the use of MOFs in energy‐related applications, for electroacoustic or resistive sensing devices . Besides that, a roadmap for the integration of MOFs into electronic devices and chemical sensors was already proposed in 2011 and updated in 2017 .…”
Section: Function and Properties Of Mofsmentioning
confidence: 99%
“…We here like to refer to a conceptual article on guest@MOF systems, published by Allendorf and our group . Additionally, there are other illuminating articles that specifically address the use of MOFs in energy‐related applications, for electroacoustic or resistive sensing devices . Besides that, a roadmap for the integration of MOFs into electronic devices and chemical sensors was already proposed in 2011 and updated in 2017 .…”
Section: Function and Properties Of Mofsmentioning
confidence: 99%
“…In addition, precise control of the distance of the chromophore can efficiently avoid the aggregation -induced fluorescence quenching in the MOFs. [73][74][75][76][77][78][79][80] Harnessing the advantages of MOFs, one can begin the development of TTA-UC MOFs to create a new type of upconversion material. As shown in Figure 12, Park et al reported a low toxicity TTA-UC MOF and applied in in vivo bioimaging.…”
Section: 5mentioning
confidence: 99%
“…As propriedades físicas e químicas características das MOFs tornam-nas materiais relevantes para uma gama de aplicações. [164][165][166] Importantes e atuais trabalhos de referencia nas áreas de biomedicina, [167][168][169][170] fotônica, 28,171-173 adsorção 174,175 e separação de gases, 176,177 catálise, 26,[178][179][180] entre outras, [181][182][183] O hidrogênio pode vir a ser uma matriz energética muito eficiente que apresenta água como subproduto de sua combustão. Já o dióxido de carbono e o metano são os principais gases estufa causadores do aquecimento global.…”
Section: Mofs Energia E Meio-ambienteunclassified